THE EFFECT OF MACRO ECONOMY AND FINANCIAL PERFORMANCE ON STOCK PRICE WITH EARNING PER SHARE AS THE INTERVENING VARIABLE (A STUDY ON RETAIL TRADING COMPANY IN IDX IN 2011-2018) - Rahadian Rachman, Rendra; Sudjono; Saluy, Ahmad Badawy (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The present study aimed to analyze a macro economic effect - proxied by BI rate, exchange rate, Foreign Direct Investment (FDI)- and financial performance - proxied by current ratio (CR), net profit margin (NPM), and debt to equity ratio (DER)- on stock price, using Earning per Share (EPS) as the intervening variable. The object of the study was retail company listed on Indonesia Stock Exchange in 2011-2018. The study used data from financial statement, BI rate fluctuation, rupiah exchange rate, FDI volume, and stock price in 2011-2018. In this study, path analysis and linear regression analysis were done using SPSS 21. The result of the study showed that, partially, BI rate and EPS positively and significantly affected stock price. While exchange rate, FDI, NPM, and DER positively, yet not significantly. Whereas Current ratio negatively and not significantly affect the stock prices. The path analysis result showed that it was only CR and DER that affected stock prices through EPS.